Depletion of Nesprin-2 is associated with an embryonic lethal phenotype in mice. (31st December 2018) - Mroß, Carmen; Marko, Marija; Munck, Martina; Glöckner, Gernot; Motameny, Susanne; Altmüller, Janine; Noegel, Angelika A.; Eichinger, Ludwig; Peche, Vivek S.; Neumann, Sascha
ABSTRACT: Nesprin-2 is a nuclear envelope component and provides a link between cytoskeletal components of the cytoplasm and the nucleoplasm. Several isoforms are generated from its gene Syne2 . Loss of the largest isoform Nesprin-2 Giant in mice is associated with a skin phenotype and altered wound healing, loss of C-terminal isoforms in mice leads to cardiomyopathies and neurological defects. Here we attempted to establish mice with an inducible knockout of all Nesprin-2 isoforms by inserting shRNA encoding sequences targeting the N- and C-terminus into the ROSA26 locus of mice. This caused early embryonic death of the animals harboring the mutant allele, which was presumably due to leaky expression of the shRNAs. Mutant embryos were only observed before E13. They had an altered appearance and were smaller in size than their wild type littermates. From this we conclude that the Nesprin-2 gene function is crucial during embryonic growth, differentiation and organogenesis.